Review of Indicators for Localizing Environmental Goals at Sub National and Local Level in Nepal - Sigdel, Ek Raj; Keitsch, Martina Maria (Journal of the Institute of Engineering, 2020)
Nepal, as a member of the United Nations, is committed to achieve the global initiatives of Sustainable Development Agenda by 2030. Toward translating the commitment into action, Nepal has produced preliminary SDGs Report in 2015, even before the formal adoption of the 2030. Moreover, Voluntary National Review Report, Sustainable Development Goals, Status and Roadmap: 2016-2030, and Sustainable Development Goals 2016-2030 National (Preliminary) Report were developed. Further, Nepal has initiated mainstreaming the 2030 Agenda into national policies and plans. The 14th periodic plan, the national budget, and other sectoral plans have been closely aligned with the SDGs and the approach paper for 15th five-year plan is intended to achieve the SDG. The upcoming 15th periodic plan will basically aim to support the government in achieving all the SDGs by 2030 and help Nepal emerge as a middle-income country by 2030. The indicators comprise of renewable energy for electricity and vehicles, injuries due to disaster (number), greenhouse gases, adaptation plans, trained man power, climate change educations, and climate smart villages and farming are identified as indicators under climate and energy goals. Similarly, under forest goals proportion of forest land, forest under community-based management (% of total dense forest areas), protected area (including forest, in % of total land area), handover of forests to leasehold forest groups (000 hectare), wild tigers (number), rhino (number) etc are included. Likewise, conservation of lakes, wetlands, and ponds (number) and potentially dangerous lakes (%) are included under fresh water goals. However, there was no scientific basis how the indicators were derived for the environmental goals. In this backdrop, a study in identifying site specific, measurable, time bound, relevant and attainable indicators was paramount. Based on the secondary literature review, stakeholder consultation at sub national and local level, the indicators were verified and suggested strategies that help localizing the environmental indicators at sub-national and local level in Nepal. The study was therefore centered on reviewing the environmental indicators and suggest appropriate strategies so that it helps expediting localization of SDG in Nepal.